THE INFLUENCE OF READING STRATEGY AND SELF-EFFICACY ON STUDENTS’ READING COMPREHENSION (A CORRELATIONAL STUDY AT A STATE ISLAMIC SENIOR HIGH SCHOOL IN PEKANBARU) - Witri, Hildayanti - (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2022)
This research was aimed to investigate the influence of reading strategy and self-efficacy on students’ reading comprehension at State Islamic Senior High School 3 Pekanbaru. The sample was taken by using cluster random sampling technique and determined sample size by using the Slovin formula. The total population was 174 students in five classes and total sample was 70 students in two classes. Inferential analysis namely simple and multiple regressions were used to analyze the data by using SPSS 22 software program. The results showed that alternative hypotheses (Ha1, Ha2, and Ha3) were accepted and null hypotheses (Ho1, Ho2, and Ho3) were rejected. First, there was a significant influence of reading strategy use on students’ reading comprehension with score 0.000 < α = 0.05. It categorized into positive and moderate relationship level that contributed as much as 28.3% to reading comprehension. Second, there was a significant influence of self-efficacy on students’ reading comprehension with score 0.000 < α = 0.05. It categorized into positive and strong relationship level that contributed as much as 46.5% to reading comprehension. Third, there was a significant influence of reading strategy use and self-efficacy simultaneously on students’ reading comprehension with score 0.000 < α = 0.05. It categorized into positive and strong relationship level that contributed simultaneously as much as 50% to reading comprehension.